ANALISIS PENGARUH SISTEM REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PADA PT.BINTANG INTERNASIONAL MAKASSAR - Risman Risman (Universitas Ichsan Sidenreng Rappang, 2025)
Analysis of the Effect of Reward and Punishment Systems on Employee Performance at PT Bintang Internasional Makassar, The main focus of this study is to determine whether the implemented reward and punishment systems can have a positive impact on improving employee performance, both partially and simultaneously. This study used a quantitative approach with multiple linear regression analysis. Data were collected through questionnaires distributed to 53 respondents and analyzed using SPSS software. The results showed that the reward variable had a positive but insignificant effect on employee performance. Punishment also did not show a significant effect on performance. Simultaneously, rewards and punishment did not significantly influence employee performance, with a coefficient of determination (R²) of 6.7%. This indicates that both variables can only explain a small portion of the variation in employee performance, while the majority is influenced by factors outside the model. These findings provide a basis for management to conduct a more comprehensive evaluation of performance improvement strategies.